Energy and environmental impact analysis of rice cultivation and straw management in northern Thailand - Sanwasan Yodkhum (2018)
© 2018 Springer-Verlag GmbH Germany, part of Springer Nature Rice cultivation and energy use for rice production can produce the environmental impacts, especially related to greenhouse gas (GHG) emissions. Also, rice straw open burning by farmers generally practiced after harvesting stage in Thailand for removing the residues in the rice field is associated with emissions of air pollutants, especially particulate matter formation that affects human health and global climate. This study assessed the environmental burdens, consisting of GHG emissions, energy use, and particulate matter formation (PM10), from rice cultivation in Thailand by life cycle assessment (LCA) and compared the environmental burdens of rice straw management scenarios: open burning, incorporation into soil, and direct combustion for electricity generation. The data were collected from the rice production cooperative in Chiang Mai province, northern Thailand, via onsite records and face-to-face questionnaires in 2016. The environmental impacts were evaluated from cradle-to-farm gate. The results showed that the total GHG emissions were 0.64 kg CO 2 -eq per kilogram of paddy rice, the total energy use was 1.80 MJ per kilogram of paddy rice and the PM10 emissions were 0.42 g PM10-eq per kilogram of paddy rice. The results of rice straw management scenarios showed that rice straw open burning had the highest GHG and PM10 emissions. However, rice straw utilization by incorporation into soil and direct combustion for electricity generation could reduce these impacts substantially.